The Determination of Disaster-Prone Areas Based on a Multifactor Approach on the Manglayang Catastrophe Volcano Edifice, West Java, Indonesia: English - Putu Ayu Andhira; Faishal Aziz; Muhammad Ghozi; Teuku Yan Waliana Muda Iskandarsyah; Johanes Hutabarat; Hendarmawan (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Manglayang is an extinct volcano in West Java characterized by a horseshoe-shaped amphitheater morphology, suggesting a past volcanic sector collapse that generated debris-avalanche deposits. This study aims to identify evidence of sector collapse, characterize debris-avalanche deposits, and delineate stable, susceptible, and hazardous landslide zones. The methodology combines Digital Elevation Model (DEM) data, Desaunettes landform classification, geological field observations, lithological analyses, and slope stability assessment. The results reveal a southeast-facing amphitheater interpreted as the main sector-collapse scar. Hummocky landforms are widely distributed between 2 – 6 km from volcnic cone and supported by debris-avalanche deposits characterized by volcanic breccias with jigsaw-crack structures and abundant large boulders. The integration of geomorphological, lithological, and geotechnical parameters indicates that steep hilly terrains represent the highest landslide susceptibility, whereas hummocky terrains are generally stable under present conditions. The proposed multifactor approach provides a comprehensive framework for reconstructing ancient volcanic collapse processes and improving disaster-prone area mapping in extinct volcanic terrains.